Measuring Learning Discipline with Peer Group Assessment of Engineering Vocational High School Students in Bali Province - I Gede Ratnaya (Journal for Lesson and Learning Studies, 2023)
Involving students through group assessment helps them to build good discipline in the learning process in the classroom. The purpose of this study was to develop an instrument of learning discipline for SMK students using the peer group assessment method, to measure student learning discipline, and to look for the influence of learning discipline on learning outcomes for SMK students. Quantitative research method used in this study. The research was carried out for one year. The research population is students of State Vocational Schools in the Province of Bali. The sample of this research is 375 students determined by using cluster random sampling. The peer group assessment method assessment instrument was developed based on the Borg and Gall development model. The data collection on the results of the learning discipline assessment was carried out by distributing questionnaires using the peer group assessment method. The results of this study were very surprising, namely 3% of students had very good learning discipline, 31% of students had good learning discipline, 25% of students had good learning discipline, and 41% of students had bad learning discipline.